HEALTH AS A LEGAL CATEGORY - Stefanchuk, R.O.; Yanchuk, A.O.; Stefanchuk, M.M.; Stefanchuk, M.O. (World of Medicine and Biology, 2019)
The article discloses the meaning of the term "health" from the legal point of view. Different approaches to disclosure of the concept of the physical person’s health as a non-property benefit are analyzed. Particular attention is paid to clarifying the meaning of the concept of "health" in accordance with the open concept of health. In addition, the article criticizes the current legal definition of health from the point of view of its use in the legal field. The necessity of including not only the somatic, but also the psychic component into the notion of health content is substantiated. It is concluded that health as a personal non-property benefit should be covered by the existing somatic and mental state of the body, which is determined by the system of qualitative and quantitative medical indices.
Keywords: health; mental health; somatic health; non-property benefit; right to health; law enforcement